PENGOLAHAN LIMBAH BUAH SIWALAN MENJADI KERAJINAN POT DI DUSUN SHOBEROH, DESA DALEGAN, KECAMATAN PANCENG, GRESIK - Wiwik Dwi Pratiwi; Endang Pudji Purwanti; Raffie Alfriesgasjah; Aygasta Firstya Alliyrahmanda; Reza Permana Mustofa; Raehanah Adelia (Pusat Penelitian dan Pengabdian Masyarakat (P3M) - PPNS, 2023)
Siwalan fruit waste is waste from the Siwalan fruit that has entered senescence and is no longer suitable for consumption. One of the problems with this waste is that only some people process it to make valuable goods. Siwalan waste includes agricultural waste that will cause global warming if not processed. Global warming can cause an increase in temperature. Siwalan fruit waste can be used to make crafts in the form of plant pots, which benefit the plant soil. Plant pot crafts were made in stages by local community PKK women, from assembling the pot frame to finishing. The implementation of this community service used an outreach and training scheme. Then, after the community has received socialization and training, a post-test is given to see the understanding gained. The local community felt the benefits obtained after receiving outreach and training regarding the importance of processing agricultural waste.